Documentary heritage and collections public policies through the formation of the documental collection of the museu da companhia paulista library - Gomes, Andreza Vellasco; Oliveira, Eduardo Romero de (Univ Estadual Campinas - Sistema Bibliotecas, 2020)
The article studies the documental collection of the Museu da Companhia Paulista in Jundiai and aims to identify how the formation of the documental collection took place in order to contribute to its valuation and organization as a documentary and railway heritage. It's purpose is to identify, then, the origin of this set, the time and conditions under which it was gathered in a collection, the function and applicability of public policies in its specific case. It should be noted that the gathering of the documentary set in a collection and its historical conditions in the 1990s and 2000s reveals beyond the institution's history, the form of public management of the time. The relations established between the creation of this collection and the institutions that originated it, generate reflections on the way the patrimonial processes were managed during the privatization period.
Keywords: Document preservation; Library administration; Museum policy; Public policy